Parents’ and caregivers’ costs of community-based rehabilitation (CBR) programme for disabled children in east coast region of Peninsular Malaysia - Hasan, Haliza; Syed Junid, Syed Mohamed Al Junid; Wan Puteh, Sharifa Ezat; Abdul Aziz, Aznida Firzah; Muhammad Nur, Amrizal; Mohd Nordin, Nor Azlin; Jaafar, Nurul Anisah (2018)
Rehabilitation for disabled children requires long-term programmes which are expensive to the family. This study aimed to estimate the cost incurred by parents and caretakers of disabled children participating in the Centre-Based and Home Based Community-Based Rehabilitation (CBR) and cost of seeking alternative care. Activity-Based Costing (ABC) method was the cost analysis approach used to estimate twelve-months expenditure by 297 (160 in Centre-based and 137 in Home-based) parents and caretakers of disabled children aged 2 to 18 who attended CBR and seek alternative care. Costing was undertaken from societal perspective. Data were collected using a self-administered costing questionnaire and were presented in median (IQR) cost calculated for the 2014 institutional financial year. Results showed that the median total cost for CBR programme, including alternative care were significantly higher in Centre-Based compared to Home-Based group (RM 7,392 (6,849) vs. (RM 8,066 (36,939) (p value <0.001). The median direct and indirect costs, excluding medications and alternative care were nearly four times as high in Home-Based compared to Centre-Based (RM 2, 376 (11,228) vs. RM 608 (739) (p = <0.001). Parents and carers in Centre-Based spent RM 1,320 (1,978) on medication and supplements compared to only RM 450 (877) for those in Home-Based group. Both groups of parents and carers spent significant amount of resources on alternative care. Although, the cost of alternative care is 90.9% of the total cost for Centre-Based group compared to 55.8% in the HomeBased group, difference is not significant (p-value = 0.543). The high costs incurred for alternative care is a major economic burden to the family. Thus, further studies evaluating the cost effectiveness of alternative care for rehabilitation of disabled children are warranted.